APLIKASI MOLEMATH TERHADAP HIGHER ORDER THINKING SKILL (HOTS) PADA MATERI BENTUK ALJABAR KELAS VII SMP NEGERI 7 BATU AMPAR - Muhammad Assobirin; Marhadi Saputro; Hartono Hartono (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2023)
This research aims to produce a learning media application Molemath against Higher Order Thinking Skill (HOTS) on algebra form material grade VII SM State 7 Batu Ampar that reaches a level of validity, practicality, effectiveness. The research uses the ADDIE development design model, which consists of five basic stages, namely analysis, design, development, implementation, and evaluation. (evaluasi). The subjects in this study are students of the 7th grade of the State High School 7 Stone Ampar as many as 22 students. The instruments used in this study are validation sheets, lifts, and pre-test questions posttest. The results of the research have been obtained that the validity of the learning media of the Molemath application against HOTS in algebraic form material categorized is very valid, the practicality of the molemath learning media against HOTs in algebric forms categorized material is very practical, and the learning medium of the Ð¼Ð¾Ð»ematic application against the HOTS of algebraical form materials categorized effectively